The role of fatty acids and triglycerides in the gonads of Paracentrotus lividus from Sardinia: Growth, reproduction and cold acclimatization. (September 2017) - Sanna, Roberta; Siliani, Silvia; Melis, Riccardo; Loi, Barbara; Baroli, Maura; Roggio, Tonina; Uzzau, Sergio; Anedda, Roberto
Abstract: A detailed characterization of lipid extracts from gonads of P. lividus over a year has been performed combining GC and NMR measurements. For this purpose, sea urchins from two different Sardinian coastal areas were collected monthly. The results underlined a correlation between gonad fatty acids profiles and both water temperature and reproduction process. In particular, EPA and ARA appear to be the most altered fatty acids following seasonal changes. It is suggested that EPA could represent a biomarker of reproduction, reaching a content around 14% during gametogenesis, mainly due to an increase of the sn-1, 3 position in TAGs. On the contrary, ARA seems to play a more important role in response to cold acclimatization, which is reflected in a modulation of ARA content in the sn-1, 3 position in TAGs. Highlights: PLs and DAGs contents in P. lividus gonad lipids are very low in respect to TAGs content. PUFAs reached 43% in winter favouring TAGs mobilization to face cold effect. EPA is a biomarker of reproduction, being around 14% during gametogenesis, mainly in the sn-1, 3 regioisomer in TAGs. ARA, principally its sn-1, 3 regioisomer, seems to play a role in response to cold acclimatization.